COVID-19 and Risk of VTE in Ethnically Diverse Populations - Go, Alan S. (Chest, 2021)
BACKGROUND: Limited existing data suggest that the novel COVID-19 may increase risk of VTE, but information from large, ethnically diverse populations with appropriate control participants is lacking. RESEARCH QUESTION: Does the rate of VTE among adults hospitalized with COVID-19 differ from matched hospitalized control participants without COVID-19? STUDY DESIGN AND METHODS: We conducted a retrospective study among hospitalized adults with laboratory-confirmed COVID-19 and hospitalized adults without evidence of COVID-19 matched for age, sex, race or ethnicity, acute illness severity, and month of hospitalization between January 2020 and August 2020 from two integrated health care delivery systems with 36 hospitals. Outcomes included VTE (DVT or pulmonary embolism ascertained using diagnosis codes combined with validated natural language processing algorithms applied to electronic health records) and death resulting from any cause at 30 days. Fine and Gray hazards regression was performed to evaluate the association of COVID-19 with VTE after accounting for competing risk of death and residual differences between groups, as well as to identify predictors of VTE in patients with COVID-19. RESULTS: We identified 6,319 adults with COVID-19 and 6,319 matched adults without COVID-19, with mean ± SD age of 60.0 ± 17.2 years, 46% women, 53.1% Hispanic, 14.6% Asian/Pacific Islander, and 10.3% Black. During 30-day follow-up, 313 validated cases of VTE (160 COVID-19, 153 control participants) and 1,172 deaths (817 in patients with COVID-19, 355 in control participants) occurred. Adults with COVID-19 showed a more than threefold adjusted risk of VTE (adjusted hazard ratio, 3.48; 95% CI, 2.03-5.98) compared with matched control participants. Predictors of VTE in patients with COVID-19 included age ≥ 55 years, Black race, prior VTE, diagnosed sepsis, prior moderate or severe liver disease, BMI ≥ 40 kg/m(2), and platelet count > 217 k/μL. INTERPRETATION: Among ethnically diverse hospitalized adults, COVID-19 infection increased the risk of VTE, and selected patient characteristics were associated with higher thromboembolic risk in the setting of COVID-19.